2023
DOI: 10.1108/acmm-02-2023-2762
|View full text |Cite
|
Sign up to set email alerts
|

Surface-modified cerium oxide as a corrosion inhibitor to enhance the performance of epoxy coatings

Abstract: Purpose The study aims to investigate the anticorrosion performance of epoxy coatings using modified cerium oxide (CeO2) by terephthalic acid (CeO2-t) and fumaric acid (CeO2-f) as corrosion inhibitors. Design/methodology/approach The chemical state of CeO2-t, and CeO2-f were analyzed by infrared radiation (IR) and X-ray diffraction (XRD). The effect of different inhibitors on the coating properties was analyzed by neutral salt spray tests (NSST) and electrochemical impedance spectroscopy (EIS). Findings Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…When the compressive stress exceeded the limit that the surface could withstand, wrinkling occurred (Mao et al , 2012). At the same time, during the curing process of the coating, the evaporation of solvents creates some micropores (Dong et al , 2023).…”
Section: Resultsmentioning
confidence: 99%
“…When the compressive stress exceeded the limit that the surface could withstand, wrinkling occurred (Mao et al , 2012). At the same time, during the curing process of the coating, the evaporation of solvents creates some micropores (Dong et al , 2023).…”
Section: Resultsmentioning
confidence: 99%
“…CeO 2 and cerium salts are effective metal corrosion inhibitors and are frequently used by researchers to modify PANI fillers (Dong et al, 2023a;Dong et al, 2023b;Tavandashti et al, 2016a). The protection of PANI/CeO 2 epoxy coatings was accessed by Lei et al (2020), and results from LEIS have demonstrated the exceptional improvement of corrosion protection performance provided by the PANI/ CeO 2 /epoxy coatings.…”
Section: Active Agentsmentioning
confidence: 99%
“…For the first approach, various organic and inorganic inhibitors were added into the epoxy coating formulations (De Lima-Neto et al , 2008; Morozov et al , 2019; Toorani et al , 2021; Sanaei et al , 2017; Bahrani et al , 2018; Xavier, 2018; Nguyen et al , 2022b; Dong et al , 2023a; Dong et al , 2023b). These inhibitors were added into coating ingredients through various coating layers, such as pretreatment/primer coat/topcoat.…”
Section: Introductionmentioning
confidence: 99%